(untitled) (International Journal of Environmental Sciences, 2025)
Abstract: This study investigates the turbidity removal efficiency of three natural coagulants Moringa oleifera, Tamarind seed, and Nirmala seed—under varying pH levels using both experimental methods and Response Surface Methodology (RSM). Jar tests were conducted at pH values of 5, 7, and 9 with an initial turbidity of 100 NTU, using dosages ranging from 10 to 70 mg/L and contact times of 30, 45, and 60 minutes. The aim was to determine optimal treatment conditions and assess the suitability of each coagulant under acidic, neutral, and alkaline environments. Results indicated that Moringa oleifera demonstrated the highest removal efficiency at pH 5, achieving 97.87% turbidity reduction at 30 mg/L and 30 minutes. Tamarind seed and Nirmali seed showed maximum efficiencies of 86.11% and 80.11%, respectively, under similar acidic conditions. At neutral pH (7), Moringa remained the most effective with 92.33% removal, while Tamarind and Nirmali achieved moderate reductions. Under alkaline conditions (pH 9), all coagulants showed reduced performance, with Moringa still leading at 84.22%. RSM modeling showed high correlation between experimental and predicted values, particularly for Moringa (error <2%), validating the reliability of the model. Contour and surface plots confirmed that coagulant dosage and contact time significantly influenced removal rates, while Pareto analysis highlighted strong interaction effects between pH and dosage. Overall, the findings establish Moringa oleifera as the most effective and consistent natural coagulant across varying conditions, followed by Tamarind and Nirmali, which can also perform well when optimized. The use of RSM significantly enhanced process optimization and predictive capability. These results support the adoption of natural coagulants as eco-friendly, low-cost alternatives in decentralized and rural water treatment applications.